Efficacy of calibration function by CMOS digital system software for working length estimation - Mohtavipour Seyedeh Tahereh; Seyedeh Saeideh Mohtavipour; Alieh Sadat Javadzadeh Haghighat; Shiva Sadeghi; Maryam Rezvani; Bahar Mahmoud Khalesi (Tehran University of Medical Sciences, 2016)
Background and Aims: Estimating the canal length is essential for reaching to a proper endodontic treatment. Any error and miscalculation in estimation of the working length, especially in curved canals, can result in complication during and after root canal therapy. The introduction of digital radiography has enabled us to measure curved canal length. The purpose of this study was to evaluate the calibration tool of Complementary Metal Oxide Semiconductor (CMOS) digital system in estimation of working length. Materials and Methods: In this in-vitro study, 80 extracted molar teeth were selected and randomly divided into three groups based on angle and radius of canal curvature. A 5 mm orthodontic wire was placed on the lateral surface of the root. Conventional radiographs were taken after insertion of endodontic file in the apical third of root canals. Radiographic images were scanned and imported to the software of CMOS digital system. Two observers estimated the file lengths with and without using calibration tool of digital measurement software. The correlation between observers was evaluated and then data were analyzed using Paired T-test with 95% confidence. Results: Overall agreement between observers was good. There was no significant difference between the mean values of calibrated measurement and true file length in the basis of canal curves (P>0.001). However, there was significant difference between the mean values of uncalibrated measurement and true file length in the basis of canal curvature (P<0.001). Conclusion: The calibrated measurement of file length was more accurate than that of the uncalibrated file length measurement.